Sistema de informações geográficas aplicado à espacialização da capacidade de uso da terra - Campos, Sérgio [UNESP]; Nardini, Rafael Calore [UNESP]; Barros, Zacarias Xavier de [UNESP]; Cardoso, Lincoln Gehring [UNESP] (FapUNIFESP (SciELO), 2010)
This research aimed to study land use capability classes in Pratânia, São Paulo State, Brazil, by using the Geographic Information System (GIS), in order to find out the appropriate planning system for soil use. The watershed covers an area of 21,773.61 ha and is located among the coordinates 22°44'48S and 22°52'17S and 48°38'21W and 48°48'07W. The land use capability map was made from the slope and soil maps, based on the features of each kind of soil and the land use capability table for class assessment. It was possible to conclude that IIIs was the most significant subclass. Slope classes from 0% to 20% were present in more than 97% of Pratânia, being the plane areas the most representative ones (55%). GIS showed to be an excellent tool for determining land use capability, because the geoprocessing use facilitates and activates the digital data crossing, allowing its storage for future environmental planning.
Geographic information system applied to spatial distribution of land use capability
Keywords: GIS; Remote sensing; Soil occupation